2007
DOI: 10.2741/2329
|View full text |Cite
|
Sign up to set email alerts
|

Targeting tumors with hypoxia-activated cytotoxins

Abstract: This review focuses on the recent development of hypoxia-activated cytotoxins. Such drugs are prodrugs activated to cytotoxic products in the hypoxic environment of solid tumors (so-called "bioreductive prodrugs"), but can also be activated by radiation (radiation-activated prodrugs). These compounds grew out of research on hypoxic radiosensitizers, which are compounds that can overcome the radiation resistance of hypoxic cells, and we will discuss this area also. The advantages and limitations of each class o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 143 publications
(108 reference statements)
0
40
0
Order By: Relevance
“…A related approach is based on the targeting of hypoxia. Hypoxia-activated prodrugs or bioreductive drugs are designed to deliver a cytotoxic agent to hypoxic areas within a tumour [140][141][142][143]. Several clinical trials have shown promising results for this class of drugs, e.g.…”
Section: Exploiting the Ph/tumour Microenvironment/ Metabolism Inter-mentioning
confidence: 99%
“…A related approach is based on the targeting of hypoxia. Hypoxia-activated prodrugs or bioreductive drugs are designed to deliver a cytotoxic agent to hypoxic areas within a tumour [140][141][142][143]. Several clinical trials have shown promising results for this class of drugs, e.g.…”
Section: Exploiting the Ph/tumour Microenvironment/ Metabolism Inter-mentioning
confidence: 99%
“…HSVtk/GCV and NTR/CB1954 have been widely used in a number of cytotoxic gene therapy studies, including therapies targeting hypoxia. [21][22][23][24] Only a few studies have compared both HSVtk and NTR systems in parallel, but none of these comparisons has been under hypoxic conditions with different transcriptional regulation. In one study, HSVtk/GCV showed the widest therapeutic index, whereas NTR/CB1954 demonstrated a stronger bystander effect in a retroviral vector.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, a large body of evidence has been accrued that establishes hypoxic regions within tumors as being populated by cells that are chemo-and radio-resistant. 1,2,29,30 Hence, the design of therapeutic agents that specifically target hypoxic tumor regions has been considered an important cancer therapy. Strategies include radiosensitizers and bioreductive drugs, which are developed on the basis that hypoxic cells have increased reductive potential.…”
Section: Discussionmentioning
confidence: 99%
“…This enhanced survival likely promotes malignant transformation and generates the characteristic chemoand radio-resistance properties that hinder therapeutic intervention. 2 The modulation of gene expression by HIF-1a and HIF-2a is mediated by their binding to HREs within the promoter and the 3 0 UTR regions of target genes. 3,12 The use of synthetic variants of this element, usually as a tandem oligomer, fused to a minimal promoter has now been extensively reported for hypoxia-inducible transgene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation